International Marketing : Strategy planning, market entry & implementation. - Bennett, Roger, 1948 April 9-; Blythe, Jim. (London : Kogan Page, 2002)
Topics covered in this third edition include international marketing research, entering foreign markets, export methods and procedures, international product policy and international advertising. Case examples and a regional analysis of individual world markets are provided.
Previous ed.: 1998.
Includes bibliographical references and index.
Keywords: Export marketing